KEADILAN SUBSTANTIF DALAM HAK WARIS PEREMPUAN: TELAAH ATAS PENDEKATAN KEPENTINGAN UMUM DAN MUSYAWARAH KELUARGA DALAM HUKUM ISLAM DAN HUKUM PERDATA - Didit Darmawan; Taufan Hamim Fitroni (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
This study conducts a literature review on the realization of substantive justice for women's inheritance rights by analyzing the approach of public interest (maslahah mursalah) in Islamic law and the mechanism of family deliberation in both Islamic and Civil law systems. The research employs a qualitative method with content analysis of primary legal texts and secondary academic literature. The findings reveal that the public interest approach within the framework of maqasid al-shariah provides a robust methodological foundation for interpreting inheritance provisions beyond rigid textual formulas. This approach enables the adaptation of inheritance distribution to contemporary socio-economic realities, ensuring that the higher objectives of law protection of life, property, and lineage are genuinely fulfilled. Concurrently, family deliberation emerges as a strategic institution bridging formal legal rules and the substantive justice demands of heirs. Effective deliberation, characterized by equal participation of all family members including women, information transparency, and mutual respect, produces agreements that are perceived as fair by all parties. The dialectic between Islamic and Civil law within family deliberation practices reveals significant convergence: both systems recognize immutable basic provisions while simultaneously opening space for creative agreements through consensus. This synergy between the public interest approach and family deliberation offers a comprehensive pathway toward substantive justice in inheritance distribution, positioning women as active subjects whose needs and contributions are duly acknowledged. The study contributes theoretically to legal discourse on substantive justice and offers practical recommendations for judges, mediators, religious leaders, and policymakers to facilitate more equitable inheritance practices.